DUXAP8 Promotes LPS-Induced Cell Injury in Pulpitis by Regulating miR-18b-5p/HIF3A - Ying Dai; Guihong Xuan; Min Yin (Elsevier, 2023)
ABSTRACT: Background: The dysregulated long noncoding RNAs (lncRNAs) are implicated in progression of various diseases, including pulpitis. Double homeobox A pseudogene 8 (DUXAP8) has been found to be upregulated in pulpitis. Herein, the functional mechanism of DUXAP8 in lipopolysaccharide (LPS)-induced pulpitis was explored. Material and methods: DUXAP8, microRNA-18b-5p (miR-18b-5p), or hypoxia-inducible factor 3A (HIF3A) levels were examined through reverse transcription-quantitative polymerase chain reaction assay. Cell behaviours were determined by Cell Counting Kit-8 assay for cell viability, Ethynyl-2'-deoxyuridine (EdU) assay for cell proliferation, and flow cytometry for cell apoptosis. Protein levels were measured using western blot. Inflammatory reaction was analysed via enzyme-linked immunosorbent assay. Oxidative stress was assessed by commercial kits. Dual-luciferase reporter assay, RNA immunoprecipitation assay, and pull-down assay were used for validation of interaction between targets. Results: Cell apoptosis, inflammatory reaction, and oxidative stress were induced by LPS in human dental pulp cells (HDPCs). DUXAP8 upregulation and miR-18b-5p downregulation were found in pulpitis. LPS-induced cell injury was relieved after downregulation of DUXAP8. DUXAP8 interacted with miR-18b-5p. The regulation of DUXAP8 was related to miR-18b-5p sponging function in LPS-treated HDPCs. HIF3A served as a target of miR-18b-5p. MiR-18b-5p protected against LPS-induced cell injury through targeting HIF3A. DUXAP8 targeted miR-18b-5p to regulate HIF3A level. Conclusions: Results demonstrated that LPS-induced cell injury in pulpitis was promoted by DUXAP8 through mediating miR-18b-5p/HIF3A axis.